Demographic and anthropometric characteristics and their effect on the concentration of heavy metals (arsenic, lead, chromium, zinc) in children and adolescents. Issue 2 (February 2023) - Hashemi, Majid; Rajabi, Saeed; Eghbalian, Mostafa; Suliburska, Joanna; Nasab, Habibeh
Abstract: Background: Biomonitoring is a well-established method for assessing people's exposure to contaminants in the environment. Many non-communicable diseases can be prevented or aggravated by physiologically monitoring heavy metals in biological matrices such as urine, evaluating their association with non-communicable diseases, and attempting to limit exposure to them. The focus of this research was to determine the association between potentially toxic elements (PTE) such as arsenic (As), lead (Pb), chromium (Cr), and zinc (Zn) urine concentrations and anthropometric indices and demographic data in children and adolescents aged 6–18 years in Kerman, Iran. Methods: 106 children and adolescents aged 6–18 years in Kerman were randomly selected. A questionnaire was used to acquire demographic information from the participants' parents. Height, weight, and waist circumference (WC) were all assessed, as well as body mass index (BMI) and BMI Z-score. Induced Coupled Plasma Mass Spectrometry (ICP/MS) was used to quantify As, Pb, Cr, and Zn concentrations in participants' urine. Results: The geometric mean concentrations were As (38.72 ± 39.30), Pb (19.58 ± 22.91), Cr (1.06 ± 0.28), and Zn (344.72 ± 288.16) μg/creatinine. Boys aged 12–18 years old had higher mean concentration of As than boys aged 6–11 years old (p = 0.019) according to two measurement standards, μg/L, and μg/creatinine, whereas girls had no significant difference. In general, there was a strong association between parental education and metal concentrations of As, Pb, and Cr. As, Pb, and Zn (μg/creatinine) had a significant positive association with BMI z-score and BMI. As, Pb, and Zn metals were shown to have a substantial positive association (p < 0.001). There was no evidence of an association between the metals evaluated and WC. Conclusions: The findings of this study generally showed that there was a significant association between demographic characteristics and exposure to these metals in children and adolescents, indicating that these people were exposed to these metals, which can harm their health. As a result, the pathways of exposure to metals must be limited. Graphical abstract: Image 1